The Liebenberg syndrome: in depth analysis of the original family. (November 2014) - Mennen, U.; Mundlos, S.; Spielmann, M.
The Liebenberg syndrome was first described in 1973 in a five- generation family. A sixth generation was added in 2001, and in 2009 a hitherto unknown branch of the same family with similar anomalies extended the family tree significantly. This article describes the clinical findings and illustrates the abnormalities with radiographs and three-dimensional computed tomography scans. We discuss the genetic abnormality that causes Liebenberg syndrome, the genomic rearrangement at the PITX1 locus on chromosome 5.The structural variations seem to result in an ectopic expression of paired-like homeodomain transcription factor 1 (PITX1) in the forelimb causing a partial arm-to-leg transformation in these patients.